Challenges of Big Data: Current Analysis (International Journal of Engineering and Computer Science, 2018)
In today’s technology, the internet has made new sources of vast amount of data available to business executives. Big data is certainly one of the biggest buzz phrases in IT today.It is comprised of datasets too large to be handled by traditional database systems. Big data refers to data volumes in the range of exabytes (1018) and beyond. Such volumes exceed the capacity of current on-line storage systems and processing systems. To remain competitive business executives need to adopt the new technologies and techniques emerging due to big data. We outline some of the challenges of big data in various big sectors. The researcher focuses how Hadoop provides fully functional end to end solutions that address a real world problem. And also this paper indicates the way to success of industries with big data technology